3
$\begingroup$

Im working on some partial fraction calculus 2 homework problems and I am having some issues with one problem. The question reads:

Evaluate the integral $\displaystyle \int\dfrac{2-(5x^2+x)\;dx}{(x-1)(x+1)^2}$

I approached it by splitting it into the form $$\dfrac{2-(5x^2+x)}{(x-1)(x+1)^2} = \dfrac A{x-1}+\dfrac B{x+1}+\dfrac C{(x+1)^2}.$$ Then I solved for $A,B$ and $C$ to get $A=-1, B=-2$ and $C=1$. Then I plugged those values back into the form I set up and started to solve for $$\displaystyle \int\dfrac{2-(5x^2+x)\;dx}{(x-1)(x+1)^2} = - \ln|x-1|-2 \ln|x+1|-\dfrac 1{x+1}+C.$$ When I entered that answer to my online homework it said that it was incorrect and I don't understand why. Hopefully someone can point out where I when wrong and possibly explain how to answer this problem correctly. Thank you!

$\endgroup$
  • 1
    $\begingroup$ Your partial fractions expansion is incorrect, you should have $B=-4$. $\endgroup$ – youler Mar 2 '14 at 20:11
  • $\begingroup$ user124539: In case you don't know about accepting an answer to the questions you ask: you can accept at most one answer per question asked. To accept an answer, simply click on the grey $\large \checkmark$ to the left of the answer you'd like to accept. It turns green when you click on it. And you receive 2 reputation points for each accepted answer. $\endgroup$ – Namaste Mar 3 '14 at 13:37
2
$\begingroup$

Your answer is very close except the constant multiplied by $\ln|x + 1|$. First, look at

$$\dfrac{2 - x - 5x^2}{(x - 1)(x + 1)^2} = \dfrac{A}{x - 1} + \dfrac{B}{x + 1} + \dfrac{C}{(x + 1)^2}$$

Multiply both sides by $(x - 1)(x + 1)^2$ to get

$$2 - x - 5x^2 = A(x + 1)^2 + B(x - 1)(x + 1) + C(x - 1)$$

If $x = 1$, then $A = -1$. If $x = -1$, then $C = 1$. Finally, $B = -4$ because

$\begin{aligned} A(x + 1)^2 + B(x - 1)(x + 1) + C(x - 1) &= Ax^2 + 2Ax + A + Bx^2 - B + Cx - C\\ &= x^2(A + B) + x(2A + C) + (A - B - C) \end{aligned}$

which implies that if $A + B = -5$, then $B = -4$ (also works for $A - B - C = 2$). So we get

$$\int \left(-\dfrac{1}{x - 1} - \dfrac{4}{x + 1} + \dfrac{1}{(x + 1)^2} \right)\,dx$$

Thus, the answer is

$$-\ln|x - 1| - 4\ln|x + 1| - \dfrac{1}{x + 1} + \mbox{C}$$

$\endgroup$
  • $\begingroup$ Thank you so much for you're help, I really really appreciate it!! $\endgroup$ – user124539 Mar 2 '14 at 21:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.